The Effect of Saline Coolant on Temperature Levels during Decortication with a Midas Rex: An in Vitro Model Using Sheep Cervical Vertebrae - Livingston, Asher; Wang, Tian; Christou, Chris; Pelletier, Matthew H.; Walsh, William R. (Frontiers in Surgery, 2015)
Decortication of bone with a high speed burr in the absence of coolant may lead to local thermal necrosis and decreased healing ability which may negatively impact clinical outcome. Little data is available on the impact of applying a coolant during the burring process. This study aims to establish an in vitro model to quantitatively assess peak temperatures during endplate preparation with a high speed burr. Six sheep cervical vertebrae were dissected and mounted. Both end plates were used to give a total of 12 sites. Two thermocouples were inserted into each vertebra, 2mm below the end plate surface and a thermal-camera set up to measure surface temperature. A high speed burr (Midas Rex, Medtronic, Fort Worth, TX) was used to decorticate the bone in a side to side sweeping pattern, using a matchstick burr (M-8/9MH30) with light pressure. This procedure was repeated while dripping saline onto the burr and bone. Data was compared between groups using a student t-test. Application of coolant at the bone-burr interface during decortication resulted in a significant decrease in final temperature. Without coolant, maximum temperatures 2mm from the surface were not sufficient to cause thermal osteonecrosis, although peak surface temperatures would cause local damage. The use of a high speed burr provides a quick and effective method of vertebral end plate preparation. Thermal damage to the bone can be minimised through the use of light pressure and saline coolant. This has implications for any bone preparation performed with a high speed burr.